Aplicación movil para el seguimiento y control de los tratamientos clínicos de la clínica “Salud Integral Farmédica s.a.c” de Trujillo - Infante Quispe, Antony Eli (2019)
This research work entitled "MOBILE APPLICATION FOR THE MONITORING AND CONTROL OF CLINICAL TREATMENTS OF THE CLINIC" HEALTH INTEGRAL PHARMÉDICA SAC "OF TRUJILLO", this work is developed with the aim of improving the monitoring and control of clinical treatments, and improve the doctorpatient relationship in the clinic. It starts from the description of the problematic reality in the clinic, considering the specific problems that in later chapters will be addressed, the main operative processes in the clinic are identified to rule the project in some of these processes, it is in these processes that are fixed the user stories to make the proposed mobile application. It also specifies the objectives that are posed to achieve with the development of the application, with the implementation of the proposed is intended to effect the monitoring of clinical treatment in the "CLINICA SALUD INTEGRAL FARMEDICA S. A. C. of Trujillo", taking as area of research the development of mobile applications and great progress in mobile devices. For the elaboration of the system and the documentation, and to fulfill the objectives, it was used as an agile development methodology Scrum. Additionally technology is used as Laravel Framework, PhpStrom, Xampp, MySql database manager, Android Studio platform. In this way it was possible to conclude satisfactorily with the implementation of the mobile application, with this application it was possible to carry out the monitoring and control of clinical treatments in the Clinic Farmedica S. A. C. and improve the relationship between the doctor and the patient.